Correlation Between Serum Malondialdehyde Levels and Disease Activity in Patients with Mild to Moderate Systemic Lupus Erythematosus - Hartanto, Kristian; Kurniati, Nova; Theodorus; Yuniza; Salim, Eddy Mart (Sriwijaya Journal of Medicine, 2025)
Systemic lupus erythematosus (SLE) is characterized by persistent inflammation and oxidative stress, which contribute to the progression of the disease.   Lipid peroxidation is indicated by malondialdehyde (MDA).   The objective of this investigation was to evaluate the correlation between serum MDA levels and disease activity in patients with mild to moderate systemic lupus erythematosus (SLE).   This investigation was a cross-sectional correlation analysis that employed baseline data from adult patients with systemic lupus erythematosus who were receiving conventional treatment.   Spearman's correlation was employed to determine the relationship between serum MDA levels and disease activity, which was evaluated using the MEX-SLEDAI score.   The study encompassed 38 patients with mild to moderate SLE.   The MEX-SLEDAI score was 3 (range 2–7), and the median serum MDA concentration was 1.42 µmol/L (range 0.90–1.99).   Spearman's correlation analysis demonstrated a moderately positive correlation between serum MDA levels and MEX-SLEDAI scores (r = 0.415, p = 0.010), indicating that elevated oxidative stress is associated with increased disease activity in SLE patients.   A considerable positive correlation between serum malondialdehyde levels and disease activity is statistically significant in patients with mild to moderate systemic lupus erythematosus (SLE).   These results support the existence of oxidative stress in the pathophysiology of lupus and suggest that MDA may serve as a potential biomarker for disease monitoring.